2011
DOI: 10.1021/ol200091k
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Thia-Sommelet−Hauser Rearrangement: Application to the Synthesis of Oxindoles

Abstract: A series of 3-arylthio-1,3-disubstituted-oxindoles were prepared in good yields by the reaction of α-diazocarbonyl compounds and sulfenamides. The reaction involves a Rh-catalyzed thia-Sommelet-Hauser-type rearrangement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(38 citation statements)
references
References 79 publications
0
38
0
Order By: Relevance
“…Next, the fluoride‐induced S–H rearrangement was developed and studied by Sato and Shirai's group in 1985–1999. Later, further reports on this rearrangement were quite limited . In 2007, my co‐workers and I successfully demonstrated that the asymmetric rearrangements of N ‐benzylic ammonium ylides using a chiral auxiliary undergo exclusively the S–H rearrangement.…”
Section: Discussionmentioning
confidence: 99%
“…Next, the fluoride‐induced S–H rearrangement was developed and studied by Sato and Shirai's group in 1985–1999. Later, further reports on this rearrangement were quite limited . In 2007, my co‐workers and I successfully demonstrated that the asymmetric rearrangements of N ‐benzylic ammonium ylides using a chiral auxiliary undergo exclusively the S–H rearrangement.…”
Section: Discussionmentioning
confidence: 99%
“…1 H NMR and 13 C NMR spectra were recorded on a Varian VNS or DPX (600 or 300 and 150 or 75 MHz, respectively) spectrometer in CDCl 3 , DMSO-d 6 , or acetone-d 6 using d ¼ 7.24 and 77.00 ppm or 2.5 and 39.5 ppm or 2.05 and 29.8 ppm as the internal standard solvent chemical shis, respectively. 20 All other reagents and solvents were purchased at the highest commercial quality and used without further purication.…”
Section: Methodsmentioning
confidence: 99%
“…[5][6][7][8][9] Representative approaches include Gassman synthesis via a thia-Sommelet-Hauser rearrangement from anilines as the key step (path a, Scheme 1) 5 and a reaction of diazocarbonyl compounds with aniline derivatives followed by thia-Sommelet-Hauser rearrangement (path b, Scheme 1). 1 Among these, oxindoles bearing heteroatoms as substituents at the C3 position are particularly important and useful in medicinal chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Wang, Zhang et al. developed a Rh(OAc) 2 ‐catalyzed thia‐Sommelet–Hauser rearrangement that led to the formation of 3‐arylthiooxindoles in moderate to good yields 8h. However, the direct, asymmetric construction of oxindoles that have a sulfur‐containing tetrasubstituted stereocenter remains elusive.…”
Section: Methodsmentioning
confidence: 99%